Do Not Huff, Puff, or Vape That Stuff: Interstitial Airspace Disease in a Teenager - Amee A. Amin; Erica Haught; Youmna Mousattat (Hindawi Limited, 2020)
A 17-year-old previously healthy male was admitted to the hospital for intractable and persistent vomiting, fever, cough, abdominal pain, and intermittent diarrhea and dehydration. He presented with severe chest pain and O2 desaturations up to 80% on room air. An infectious (including a nasopharyngeal swab), GI, and cardiac workup was completed and was negative except for elevated inflammatory markers with a C-reactive protein (CRP) level of 261 mg/L, erythrocyte sedimentation rate (ESR) of 53 mm/hr, and a D-dimer level of 0.93 mcg/ml. Chest X-ray showed diffuse multifocal infiltrates. The patient was treated with ceftriaxone and azithromycin initially for a suspected pneumonia. He was also started on 4L of nasal cannula O2 supplementation. Due to persistent hypoxic respiratory failure, worsening respiratory distress clinically, with tachypnea and retractions, and lab findings of elevated D-dimer, a chest CT was performed to rule out a pulmonary embolism (PE). Computed tomography (CT) findings were negative for PE but notable for diffuse airspace opacities, primarily within the lower lobes, with a ground-glass appearance concerning for ARDS. Upon further investigation of the social history, the patient admitted to vaping nicotine products for the past 4 years and tetrahydrocannabinol (THC) products within the last several months. He was immediately started on prednisone 30 mg BID for a diagnosis of e-cigarette or vaping product use-associated lung injury (EVALI) and started showing clinical improvement. The patient was able to be weaned off of supplemental oxygen to room air, and clinical symptoms of respiratory distress began to improve over the next 24 hours.